Effect of buffer additives on solubilization and refolding of reteplase inclusion bodies - Iman Esmaili; Hamid Mir Mohammad Sadeghi; Vajihe Akbari (Wolters Kluwer Medknow Publications, 2018)
Reteplase is a non-glycosylated and recombinant form of tissue type plasminogen activator, which is produced in Escherichia coli. However, its overexpression usually leads to formation of inactive aggregates or inclusion bodies. In the present study, we report on the development of optimized processes for isolation, solubilization, and refolding of reteplase inclusion bodies to recover active protein. After protein overexpression in E. coli BL21 (DE3) inclusion bodies were isolated by cell disruption and repeated wash of pellet with buffer containing Triton X-100. To solubilize the inclusion bodies, different types, concentrations, pHs, and additives of denaturing agents were used. Rapid micro dilution method was applied for refolding of solubilized reteplase. Different chemical additives including sugars, alcohols, polymers, detergents, amino acids, kosmotropic, and chaotropic salts, reducing agents, and buffering agents were used in the refolding buffer. To evaluate the biological activity of refolded reteplase, an indirect chromogenic assay was performed. The best solubilizing agent for dissolving reteplase inclusion bodies was 6 M urea at pH 12. The optimized buffer for refolding of solubilized reteplase was found to be 1.15 M glucose, 9.16 mM imidazole, and 0.16 M sorbitol which resulted in high yield of biologically active protein. Our results indicate type, concentration, and pH of solvent and type, concentration, and combination of chemical additives can significantly influence the yield of inclusion bodies solubilization and refolding.